Homogeneity Property of Besov and Triebel-Lizorkin Spaces. (25th February 2012) - Schneider, Cornelia; Vybíral, Jan
Abstract : We consider the classical Besov and Triebel-Lizorkin spaces defined via differences and prove a homogeneity property for functions with bounded support in the frame of these spaces. As the proof is based on compact embeddings between the studied function spaces, we present also some results on the entropy numbers of these embeddings. Moreover, we derive some applications in terms of pointwise multipliers.